2014
DOI: 10.1016/j.yrtph.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in reporting of drug-associated liver injury: Data-mining of WHO Safety Report Database

Abstract: Age-specific phenotypes and potential drug properties associated with age-specific hepatotoxicity were identified in reported liver events; further analyses are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 78 publications
2
33
0
1
Order By: Relevance
“…In a population-based study done in Iceland, a relationship between DILI incidence and increasing age was observed, probably related to a greater exposure to polypharmacy in older subjects [6]. Apparently, the type of liver injury differed with age with younger patients presenting more frequently hepatocellular damage as compared to cholestatic/mixed injury seen in the old [49,51]. The risk of developing valproic acid-induced hepatotoxicity with fatal outcomes is higher in children below the age of two [52].…”
Section: Host Factors Influencing Drug Handlingmentioning
confidence: 98%
“…In a population-based study done in Iceland, a relationship between DILI incidence and increasing age was observed, probably related to a greater exposure to polypharmacy in older subjects [6]. Apparently, the type of liver injury differed with age with younger patients presenting more frequently hepatocellular damage as compared to cholestatic/mixed injury seen in the old [49,51]. The risk of developing valproic acid-induced hepatotoxicity with fatal outcomes is higher in children below the age of two [52].…”
Section: Host Factors Influencing Drug Handlingmentioning
confidence: 98%
“…The exact pathogenesis of idiosyncratic DILI and HILI is poorly understood, and the risk factors arise from three diverse aspects: (1) clinical host-related; (2) environmental; and (3) drug-related. Non-modifiable risk factors include age and gender[122]; however one must remember discrepancies in DILI reporting when citing one particular age or gender at greatest risk, for example, males have been indicated as high risk patients for DILI associated with systemic antivirals, whereas liver injury and ALF has been reported with higher frequency in children[81,123]. In any case, females have been predominately identified in many registries[71,76-79].…”
Section: Risk Factors and Natural Progression Of Dilimentioning
confidence: 99%
“…In particular, mRNA levels of MDR1 are decreased in elderly patients. The expression of MDR1 is generally heterogeneous, and this expression becomes even more pronounced with age [102, 103]. Additionally, OATP1B1 has about fourteen known mutations that have been found to exist within individual populations of people from either European, African, or Asian descent [13].…”
Section: Mechanisms For Idiosyncratic Hepatotoxicitymentioning
confidence: 99%